2019
DOI: 10.1177/1120672119880390
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography and arterial hypertension: A role in identifying subclinical microvascular damage?

Abstract: Introduction: To evaluate retinal microvasculature modifications by means of optical coherence tomography angiography in human subjects diagnosed with arterial hypertension and to assess potential clinical relevance for early diagnosis. Methods: A cross-sectional study of 30 subjects affected by arterial hypertension compared to a matched cohort of healthy patients was conducted. Patients were evaluated by the Outpatient Clinic for Hypertension and the Retina Center, University of Insubria, Varese, Italy. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 24 publications
2
69
1
5
Order By: Relevance
“…In addition to obesity, other vasculopathic risk factors like hypertension, hyperglycaemic and hyperlipidemia are possible public health conditions which may be closely correlated with ocular microcirculation. [29][30][31][32][33][34] However, results in our study did not suggest presence of hypertension, DM, elevated SBP or DBP or HbA1C or serum lipids were independently associated with the decrease of NFLP VD. The difference of sample size, inclusion criteria and race potentially contributed to the discrepancies in results.…”
Section: Clinical Sciencecontrasting
confidence: 91%
“…In addition to obesity, other vasculopathic risk factors like hypertension, hyperglycaemic and hyperlipidemia are possible public health conditions which may be closely correlated with ocular microcirculation. [29][30][31][32][33][34] However, results in our study did not suggest presence of hypertension, DM, elevated SBP or DBP or HbA1C or serum lipids were independently associated with the decrease of NFLP VD. The difference of sample size, inclusion criteria and race potentially contributed to the discrepancies in results.…”
Section: Clinical Sciencecontrasting
confidence: 91%
“…Fifth, reduced macular VD and increased foveal avascular zone in patients with hypertension have been reported 47,48 . However, the optic disc VD was shown to reduce only in patients with first diagnosis of systemic hypertension but not in patients already treated for systemic hypertension 49 . Wang et al 48 also reported decreased retinal and choroidal VD in the macular region in patients with coronary heart disease.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is consistent with that in a study performed in patients with hypertension by Donati et al . [ 37 ] who observed a significant reduction in vessel density in the deep DCP and attributed this change in the microvascular network to thinning of the retinal vessels and loss of capillaries as a result of endothelial injury. Moreover, Koulisis et al .…”
Section: Discussionmentioning
confidence: 99%